VALUATION OF THE MULTISECTION LPD ANTENNA AS AN ALTERNATIVE FOR DIGITAL TERRESTRIAL TELEVISION - Cordoví Rodríguez, Tuan Ernesto; Jiménez Hernández, Roberto; Beltrán Casanova, David (Telemática, 2020)
The following work deals with the design, manufacture, modifications and the current situation for the commercialization of a Multiband Log-Periodic Antenna proposed especially for use with a 75 Ω coaxial cable which was chosen after a brief study and technical considerations of agreement to utility, competition with foreign antennas and prices. Various prototypes have been developed in conjunction with the various technologies for their manufacture. Zero productions have been manufactured for tests and validations in some localities within the national territory that are comprised in areas with difficulties in receiving DTT. So far they have been marketed in some state entities along with their installation service by the Villa Clara Antenna Company. As a final result, a group of techno-logical considerations, criteria and market requirements to carry out the manufacturing of an antenna with high performance and intended to cover Band III of VHF, from channel 7 to 13, and UHF from channel 14 to 51 mainly for the purposes of receiving Digital Terrestrial Television (DTT).